Arabic Language Curriculum Model Based on Bugis-Makassar Local Wisdom for Madrasah Ibtidaiyah: A Study at MIS DDI Palanro - Muammira Enemsaini; Darmawati Darmawati; Nuralam Alwi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2026)
This study addresses the persistent gap between normative-textual Arabic curricula and the sociocultural realities of students embedded in Bugis-Makassar traditions. The research aims were to (1) describe the integration model of siri', pacce, and sipakatau values into the Arabic curriculum; (2) analyze the effectiveness of local wisdom-based approaches on students' motivation and linguistic competence; and (3) formulate a replicable curriculum design for similar madrasah ibtidaiyah contexts. The study was conducted at MIS DDI Palanro, Barru Regency, South Sulawesi, using a research and development (R&D) approach with the ADDIE model, reinforced by a qualitative-phenomenological approach. Data were collected through participatory observation, in-depth interviews, focus group discussions, and curriculum document analysis, then analyzed quantitatively using an independent samples t-test and qualitatively using thematic analysis. Findings indicate that integrating pangngadereng values particularly siri' and pacce into Arabic materials, methods, and assessment significantly increased student engagement by 67.3% and speaking competence (maharah al-kalam) attainment by 54.8% compared to the control group. These results confirm that local wisdom functions not merely as cultural decoration but as cognitive and affective scaffolding that accelerates Arabic language internalization. The study's implications advocate for the development of ethnopedagogy-based Arabic syllabi relevant to South Sulawesi contexts.